Abordagem clínica da atividade de trabalho do cozinheiro: interação de saberes, gênero profissional e inovação criativa - Oliveira, Samid Danielle Costa de (2011)
The focus of this dissertation is the study of work activities developed in the context of professional occupations characterized by varied previous schooling levels amongst those that work in them, and, at the same time, a high degree of complexity related to the typical tasks performed in the context of such professional practices. This dissertation intends to investigate the cook s professional activity, based on data from a determined specific professional genre in Natal (RN), in order to establish aspects related not only to the activity performed (activity which manifests itself empirically in registered behaviors), but also related to the real aspects of the work activity, that also compromises the non-realized options of the guiding of professional activity, be it by a matter of choice, be it due to the activity s own impediment. In this context, we tried to evaluate how much the professional activity observed keeps in relation to the reference practices of the professional genre, be it in terms of conformity, be it in terms of innovation (stylization) in relation to this genre. In addition, we tried to verify the contribution of the school and extra-school knowledge to the professional activity observed. Such work plan took on a preliminary step of the description of the socialprofessional profile of a cook in the city of Natal (RN), followed by a step of clinical labor approach, specifically utilizing as a methodological tool the simple and crossed self-confrontation procedure guided by the francophone theoretical referential of the Activity Clinic. The preliminary step in the description of profile of cooks from Natal (RN), of which 138 cooks took part in, evidenced three professional groupings, all predominantly masculine in their composition and fundamentally differentiated amongst each other by the time of professional activity, schooling type and time, work place and salary. The clinical approach step, composed by a pair of cooks, allowed us to verify elements of the cooks subordination to the professional genre, but also evidences of individual innovation (stylization) by these cooks, as well as the predominance of usage of extra-school knowledge when compared to school knowledge. We tried, in this step, to demonstrate how much the inclusion and submission to the genre dynamic, coordinated with the stylization initiatives, was able to contribute to the maintenance and amplification of the cook s power of acting in his professional practice.